Efficient adsorption of ofloxacin in a novel nanocomposite formed by nano-hexagonal boron nitride fused with zeolite imidazolite skeleton-8: Experimental and molecular dynamics simulation studies - Zefang Huang; Yuankai Hong; Yiqun Cui; Huiying Guo; Yan Long; Jinshao Ye (Ecotoxicology and Environmental Safety)
With the widespread application of antibiotics in the medical field, associated wastewater pollution has become a critical environmental issue, creating potential risks to ecosystems and public health. This study synthesized three novel nanocomposite materials, ZIF-8@h-BN-X, using an in-situ growth method by adjusting h-BN content. Compared to pure two-dimensional hexagonal boron nitride (h-BN), their adsorption capacities for ofloxacin (OFL) in solution were evaluated. Results showed that zeolitic imidazolate framework-8 (ZIF-8) attached and grew on the h-BN surface, altering surface functional groups and significantly enhancing the nanocomposite's adsorption effect on OFL. Adsorption capacity depended on the initial h-BN content, with lower X content resulting in more active sites and stronger adsorption capacity. Equilibrium adsorption capacities were 145.46, 124.91, and 58.16 mg·g−1 for X values of 29.82 %, 45.93 %, and 62.95 %, respectively. Molecular dynamics simulations revealed interaction energies of −109.13 kcal·mol−1 between ZIF-8@h-BN-X and OFL, compared to −84.78 kcal·mol−1 between pure h-BN and OFL, demonstrating the superior adsorption performance of ZIF-8@h-BN-X. OFL adsorption on ZIF-8@h-BN-X followed the Langmuir isotherm model and pseudo-second-order adsorption kinetics. Thermodynamic parameters indicated that the adsorption process of ZIF-8@h-BN-X was exothermic and spontaneous when compared to h-BN alone. This study highlights the significant potential of ZIF-8@h-BN-X in treating antibiotic-contaminated wastewater, while providing theoretical and practical insights for developing novel, efficient two-dimensional nanocomposite adsorbents.